0671 Effects Of Short-interval And Isolated Leg Movements In Sleep On RLS Severity And Sleep Quality In Patients With RLS. (27th April 2018) - Jun, J; Kim, M; Kim, T; Cha, K; Kim, H; Koo, S; Jung, K
Abstract: Introduction: Periodic leg movements in sleep (PLMS) are present in more than 80% of patients with restless legs syndrome (RLS). Some leg movements in sleep (LM) do not satisfy the PLMS diagnostic criteria, which are called non-periodic leg movement (NPLM). They can be classified as short-interval LM in sleep (SILMS, IMI<10s), isolated LM in sleep (ILMS, IMI>90s), and others. PLMS are associated with arousals and autonomic activation, which may contribute to higher cardiovascular disease risk in patients with RLS. Thus, the aim of this study is to evaluate clinical impacts of SILMS and ILMS in patients with RLS by comparison of heart rate related SILM, ILMS between patients and controls. Methods: In this retrospective case-control study, 10 idiopathic RLS patients and 10 controls were included. LMs were automatically detected within polysomnography (PSG). Objective sleep quality was measured with PSG findings including total sleep time, sleep latency and slow wave sleep. Subjective sleep quality was measured with Pittsburgh Sleep Quality Index (PSQI). RLS severity was measured with International Restless Legs Syndrome Study Group Rating Scale (IRLS). We assessed the correlation between frequencies of SILMS, ILMS, PLMS and RLS severity, sleep quality. In addition, correlation between heart rate associated each LM type and clinical factors was evaluated. Results: Frequencies of SILMS, ILMS and PLMS in patients with RLS were not significantly different compared to controls. However, patients presented higher heart rate associated with SILMS (p=0.011) and ILMS (p=0.026) than controls, but not heart rate associated with PLMS. Heart rate related to SILMS and ILMS were correlated with IRLS scale (r=0.7262, p=0.0188 and r=0.7632, p=0.0147, respectively) and PSQI (r=0.724, p=0.0178 and r=0.6420, p=0.0454, respectively) in patients with RLS. Heart rate associated with PLMS did not show correlation with IRLS scale in patients. Conclusion: Our results suggest that cardiac activation related to SILMS and ILMS might contribute to sleep disturbance and sensorimotor symptom in patients with RLS. Support (If Any): none.